2017
DOI: 10.2147/ijn.s141882
|View full text |Cite
|
Sign up to set email alerts
|

Photoactivatable RNAi for cancer gene therapy triggered by near-infrared-irradiated single-walled carbon nanotubes

Abstract: The efficacy of RNA interference (RNAi)-based cancer gene therapy is limited by its unexpected side effects, thus necessitating a strategy to precisely trigger conditional gene knockdown. In this study, we engineered a novel photoactivatable RNAi system, named as polyetherimide-modified single-wall carbon nanotube (PEI-SWNT)/pHSP-shT, that enables optogenetic control of targeted gene suppression in tumor cells. PEI-SWNT/pHSP-shT comprises a stimulus-responsive nanocarrier (PEI-SWNT), and an Hsp70B′-promoter-dr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2018
2018
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 26 publications
0
7
0
Order By: Relevance
“…By irradiating with NIR light, PEI-SWCNTs started to heat, and then activated the gene knockdown targeting human telomerase reverse transcriptase by RNAi. 124 Pantarotto et al synthesized a first generation of ammonium f-CNTs using it for mammalian cell pDNA delivery. Here, ionic interactions were established between the positive charges of ammonium f-CNTs and phosphate groups of pDNA, and the expression level of the β-galactosidase marker in the CHO cells was about 10 times greater than when the naked pDNA was observed.…”
Section: Dovepressmentioning
confidence: 99%
“…By irradiating with NIR light, PEI-SWCNTs started to heat, and then activated the gene knockdown targeting human telomerase reverse transcriptase by RNAi. 124 Pantarotto et al synthesized a first generation of ammonium f-CNTs using it for mammalian cell pDNA delivery. Here, ionic interactions were established between the positive charges of ammonium f-CNTs and phosphate groups of pDNA, and the expression level of the β-galactosidase marker in the CHO cells was about 10 times greater than when the naked pDNA was observed.…”
Section: Dovepressmentioning
confidence: 99%
“…Gene delivery system Improved moleculartargeted gene therapy [112] vitro research of breast cancer cell lines due to their physiological adaption and biomimetic features they displayed, according to their findings, which also revealed that they will aid in cell adhesion [103]. A study on the investigation to evaluate whether CNTs could be applied for tumour progression has been conducted by Akinoglu et al in 2017 [103].…”
Section: Optical Imagingguided Photothermal Therapymentioning
confidence: 99%
“…Additionally, their research revealed that a combination of gene therapy and photothermal therapy (Figure 6) using a photoactivatable RNAi mechanism and PEI-SWNT resulted in greater antitumor efficacy, both in vitro and in vivo. A better understanding of molecularly targeted gene therapy in human cancer cells may be made possible by optogenetic control of RNA interference according to the CNTs carried which are activated by NIR light [112].…”
Section: Optical Imagingguided Photothermal Therapymentioning
confidence: 99%
“…Heating PEI-SWCNTs in MCF-7 cells triggered gene knockdown that targeted human telomerase reverse transcriptase via RNAi in the near infrared field (NIR). The study showed that the combined effect of gene therapy and photothermal therapy of the photoactivatable RNAi system showed significant antitumor activity [101]. Due to the targeted delivery of Bcl-xL-specific shRNA and doxorubicinin, synergistic tumor cell death was achieved.…”
Section: Cnts In Gene Therapymentioning
confidence: 99%